Modern possibilities of treating brain tumors: intraoperative technologies in neurooncology - Arthur I. Nafikov; Radmir I. Minnigaleev; Elina R. Yarullina; Eminat M. Magomedova; Karina G. Soboleva; Maksim M. Sobolev; Oishakhon R. Egamova; Yulia A. Kirillova; Arut A. Arutyunyan; Fatimat A. Tokhova; Nurlana A. Abbasova; Khanipat Kh. Saadueva; et al. (Клиническая практика)
The fundamental principle of neurooncology is the maximal removal of the tumor, simultaneously minimizing the effects on the healthy brain structures. In cases of malignant gliomas, the extent of resection still remains a critical parameter, which significantly affects the prognosis of the disease. The results from numerous trials show that the increase of the resected tumor volume correlates with improved survival rates. This review provides the data on the innovative intraoperative therapeutic technologies, developed for improving the treatment outcomes among the patients with brain tumors. It is important to note that each of these technologies has its benefits and limitations. For example, laser interstitial thermotherapy provides the ability of highly precise destruction of tumor cells with minimal damaging of the surrounding healthy tissues, however, it requires special equipment and qualified personnel. Photodynamic therapy is distinguished by selective affecting the tumor, but its efficiency depends on the type of photosensibilizing agent used and on the depth of light penetration. Brachytherapy, in turn, provides the possibility of local tumor irradiation, minimizing the effects on the surrounding structures, but it can require a long-term following up the patient after the procedure. Thus, the use of modern intraoperative methods gives access to new perspectives in neurooncology, providing a more precise and sparing destruction of tumors with preserving the functional activity of the healthy brain structures. However, the success of their use depends on further development of technologies, on increasing the qualification of specialists and on the close interactions of the scientific community with the industry and with the regulating authorities.